Hydrocarbons occurrence and transcriptomic response of oyster Crassostrea virginica from lagoons of the Southern Gulf of Mexico - Edgar A. López-Landavery; Clara E. Galindo-Sánchez; Laura L. López-Galindo; Nancy Ramírez-Álvarez; Anaid Saavedra-Flores; Gerardo Amador-Cano; Claudia Ventura-López; Pablo San Martín-Del Ángel; Rosa I. Hernández-Herrera (Frontiers in Marine Science, 2023)
The Gulf of Mexico is an important crude oil reserve worldwide, and the oyster Crassostrea virginica is an excellent candidate to study the oil spill impacts on marine invertebrates. In this work, the concentrations of polycyclic aromatic hydrocarbons (PAHs) and aliphatic hydrocarbons (AHs) from eight productive oyster areas in the Gulf of Mexico were measured on sediment, water, and tissues from C. virginica . In water, the highest AHs concentration was detected in Tamiahua (0.50 ng/mL), while for PAHs, the highest concentration was > 0.10 ng/mL in Tampamachoco. In sediment, Tamiahua and Tampamachoco lagoons had the highest AHs concentrations with values near 2.5 μg/g dry weight. Considering the PAHs, Tamiahua, Carmen, and Tampamachoco lagoons registered the highest levels, with values > 60 ng/g dry weight. In tissues from C. virginica , La Pesca, Cármen and Mecoacán presented the highest PAHs concentrations with values between 0.20 and 0.25 μg/g dry weight. Furthermore, from the molecular analysis of genes related with different phases of the xenobiotic detoxification process such as hypoxia inducible factor ( hif-1a ), cytochrome P450 10 ( cyp10 ), flavin mono-oxygenase ( fmo ), glutathione S-transferase ( gstΩ1 ), multidrug resistant protein ( mdrd1 ), catalase ( cat ), among others, the differences between lagoons were significant ( P < 0.05) and generally with Las Enramadas showing the highest expression levels. From genes evaluated in this study, hif-1a , cyp10 , fmo , mdrd1 and cat presented the highest expression differentials between lagoons. The above allowed us to validate the utility of molecular markers in the assessment of the hydrocarbons effect on oyster under the conditions from the Southern Gulf of Mexico.